Biostratigraphic evidence of human modification of high elevation aquatic ecosystems in the Intermountain West of the United States. (December 2017) - Porinchu, D.F.; Haskett, D.R.; Reinemann, S.A.
Abstract: High resolution analysis of subfossil chironomid remains preserved in well-dated lacustrine sediment cores was undertaken to identify whether marked shifts in chironomid assemblages have occurred in recent decades in the Colorado Rocky Mountains. This study will improve our understanding of site-specific aquatic ecosystem variability in the central Colorado Rockies during the 20th and early 21st centuries. An observed increase in chironomid taxa associated with warmer, more productive lakes, e.g. Dicrotendipes, is consistent with the movement of these lakes towards more productive aquatic systems in recent decades. The application of a chironomid-based inference model for mean July air temperature (MJAT) to the midge stratigraphies from these sites provide centennial length reconstructions of MJAT. The chironomid-inferred reconstructions of MJAT closely track gridded MJAT estimates for much of the 20th century; however, the response of the chironomid community is muted relative to the elevated temperatures that characterize this region during the last decade. Complementary analyses of sub-fossil chironomid records, previously developed from additional high elevation lakes located throughout the Intermountain West of the United States, indicate that the rate and magnitude of faunal turnover during the late 20th and early 21st centuries surpass the rate and magnitude of faunal turnover during any preceding interval in the last century. Direct gradient analyses reveal that the chironomid assemblages in the majority of sites became increasingly similar in composition to the assemblages associated with warmer, lower elevation sites between the early 20th and early 21st century.